CORRELATION BETWEEN LISTENING SKILL AND SPEAKING ABILITY ENGLISH DEPARTMENT SECOND SEMESTER MADURA UNIVERSITY - Salasatun Husniyah; Devie Reztia Anjarani (Universitas Madura, 2020)
One of factors for student success in speaking ability is to use their listening ability, because Listening is play important in development process of speaking ability. therefore, this research aimed to finding out the correlation between students’ listening skill and speaking ability.This research applied a correlation study and used a quantitative design, the subject were 22 students of English Department second semester Madura University. There are two instruments to collect the data on this research. (1) essay test was used to get the data of their listening skill. (2) interview was used to get the data of their speaking ability.Person correlation product moment and SPSS version 26 program is used to analysis the data. The result this research shown that there is high correlation between students’ listening skill and speaking ability, which the value of